Long-term effects of the cryopreservation of turbot (Psetta maxima) spermatozoa - Suquet, Marc; Dreanno, Catherine; Petton, Bruno; Normant, Yvon; Omnes, Marie-helene; Billard, Roland (Aquatic Living Resources, 1998)
The survival of turbot eggs and the rearing capacities of larvae stemmed from artificial fertilization practices using frozen-thawed spermatozoa were evaluated. Furthermore, the viability of sperm samples stored during a 9 month period in liquid nitrogen was assessed. No significant difference in the fertilization rate, hatching rate, survival and wet weight of 10-day old larvae were observed using fresh or frozen-thawed spermatozoa. The motility recorded at 10 s and 60 s post-activation and the fertilization capacity of frozen-thawed spermatozoa were not significantly decreased during a 9 month storage period in liquid nitrogen. These results confirm the high quality of the turbot spermatozoa stemmed from the cryopreservation process, allowing their use for routine aquaculture practices.